(untitled) (Biological Sciences - PJSIR, 2020)
This study was designed to determine the best olive variety for cultivation in Pakistan. The leaves of eight locally grown varieties were analyzed for levels of moisture, total solids, ash, fat, fibre, protein, K, Ca, Mg, Na, Fe, Mn, Zn and Cu levels. Leaves were then subjected to solvent extraction with each of water ratio in, 75% ethanol, 75% methanol, 95% ethanol and 95% methanol. The extract yield was significantly highest for 75% ethanol extract of all varieties. Significantly highest polyphenol and flavonoid contents were examined for Gemlik leaves extracted with 75% ethanol. We recommend cultivation of Gemlik in Pakistan and extraction of bioactive compounds from olive leaves will be the most efficient with a binary solution of 75% ethanol in water. Further studies should be planned to assess antioxidant, antimicrobial and food preservation properties of olive leaf extract from locally grown varieties.